Total Flavonoid Content of Lemongrass Leaf (Cymbogoncitratus (DC.) Stapf) Extract and Antioxidant Activity with Frap - Ahda Maulida Ulufan Nurinnafi'a; Kusumaningtyas Siwi Artini; Desy Ayu Irma Permatasari (Journal of Fundamental and Applied Pharmaceutical Science, 2022)
Lemongrass (Cymbogoncitratus (DC.) Stapf) leaves contain alkaloids, saponins, tannins, anthraquinones, steroids, phenols and flavonoids. Flavonoids act as antioxidants as they can reduce free radicals. This study aims to determine the total flavonoid content, antioxidant activity, and IC50 value of lemongrass leaf extract (Cymbogoncitratus (DC.) Stapf). Extracts were made by maceration using 96% ethanol as solvent. Testing of total flavonoid content with the AlCl3 method using UV-Vis spectrophotometry was carried out three times. The antioxidant activity test used the FRAP (ferric reducing antioxidant power) method on extracts containing 100, 200, 300, 400, and 500 ppm. The test results showed that the leaf extract of citronella (Cymbogoncitratus (DC.) Stapf) had a total flavonoid content of 22,60 mg QE/g extract. Furthermore, there was antioxidant activity in the leaf extract of lemongrass (Cymbogoncitratus (DC.) Stapf indicated by the formation of a blue color purplish when reacted with FRAP solution, and IC50 extract value was 71,59 ppm and included in the category of strong antioxidants.